Algorithm development and validation for satellite-derived distributions of DOC and CDOM in the U.S. Middle Atlantic Bight - Mannino, Antonio; Russ, Mary E.; Hooker, Stanford B. (Journal of Geophysical Research. C. Oceans, 2008)
Oceanographic cruises were conducted within the U.S. Middle Atlantic Bight (MAB) to collect field measurements to develop algorithms to retrieve surface ocean colored dissolved organic matter (CDOM) and dissolved organic carbon (DOC) from NASA's MODIS‐Aqua and SeaWiFS satellite sensors and to investigate the processes that influence the distributions of CDOM and DOC. In order to develop empirical algorithms for CDOM and DOC, the CDOM absorption coefficient (aCDOM) was correlated with in situ remote sensing reflectance band ratios, and DOC was then derived from aCDOM through the aCDOM to DOC relationships. Our validation analyses demonstrate successful retrieval of DOC and CDOM using MODIS and SeaWiFS with mean absolute percent differences from field measurements of 9.3 ± 7.3% for DOC, 19 ± 14% for aCDOM(355), 15.5 ± 12% for aCDOM(443), and 8.6 ± 4.9% for the CDOM spectral slope. To our knowledge, the algorithms presented here represent the first validated algorithms for satellite retrieval of aCDOM, DOC, and CDOM spectral slope in the coastal ocean. Satellite imagery demonstrates the importance of riverine/estuarine discharge from Chesapeake Bay and Delaware Bay to the export of CDOM and DOC to the coastal ocean. Between spring and summer, photooxidation has a significant impact on CDOM distributions resulting in a pronounced decrease in aCDOM between the midshelf and continental slope region of the MAB. The satellite‐derived DOC products demonstrate the net ecosystem production of DOC of 12 to 34 μmol C L−1 between spring and summer. The aCDOM algorithms presented here are applicable to other coastal regions and can also be used to retrieve DOC using region‐specific aCDOM to DOC relationships.